Prevalence of Chronic Kidney Disease (CKD) and Identification of Associated Risk Factors among Rural Population by Mass Screening (Community Based Medical Journal, 2013)
The prevalence of Chronic Kidney Disease (CKD) is rapidly increasing worldwide. Population-based studies on the prevalence of kidney damage are limited in developing countries. The present work relates to a population-based screening study in a rural population. Objectives: The study was performed to investigate the prevalence of chronic kidney disease (CKD) in rural residents and find out the association of the associated risk factors and variables. Methods: This is a descriptive cross sectional study. The demographic variables included were age, sex, marital status, religion, occupation, socioeconomic status, monthly income. The clinical variable was hypertension. The risk factors under the study were Body Mass Index (BMI), smoking habit, hypertension, and diabetes mellitus. Data pertaining to biochemical investigations were urine for albumin, serum creatinine and random serum glucose. CKD suspected patients were subjected to repeat serum creatinine and urinary albumin testing three months after the initial testing to confirm diagnosis of true CKD. Results: 1240 patients of which 650 were males and 590 females, aged between 18 and 65 years were entered into this study. The result evidenced over-all CKD prevalence 19 % determined by Cockcroft-Gault and 19.5 % MDRD equations. Stage 3 CKD was found to be predominant in both Cockcroft-Gault (12.8%) and MDRD equations (13.2%). The risk factors were thought to be associated with CKD which demonstrated association with hypertension (19.3%), diabetes (4.9%) and others (1.3%). A total of 206(88%) patients determined by Cockcroft-Gault and 210 (89.4%) by MDRD equations were diagnosed as having CKD in 2nd follow up visit (3 months after the 1st visit). Conclusion: It appears from this study that one out of three people in this population at risk remained undiag-nosed as CKD and with poorly controlled CKD risk factors. This is a growing problem and a challenge to this country. On priority basis CKD needs to be addressed through the development of multidisciplinary health teams and establishment of improved communication between traditional health care givers and nephrology services. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13825 Community Based Medical Journal Vol.1(1) 2012 20-26